Development of control strategy for fast idling condition of diesel engine based on target torque. (December 2021) - Jian, Jiesong; Lin, Xuedong; Ren, Yuanchun; Zhang, Yingchao; Shen, Chun; Zhang, Chengchun
This article puts forward the concept of fast idling condition. The comparative experiments of idling and fast idling warming up engine show that: during cold start, the warm-up of fast idling condition whose maximum speed is 1350 r/min is the most fuel-efficient, fuel-saving about 4.5%, time-saving about 32.5%; at normal temperature, warming up engine of fast idling condition does not save fuel. The warm-up experiments of fast idling condition that accelerations are different in the descent phase show that when the engine is cold, the smaller the acceleration in the descent phase of fast idling condition is, the more time and fuel are saved; at normal temperature, the bigger the acceleration in the descent phase of fast idling condition is, the better the fuel economy is. Therefore, it is inferred that the engine should be warmed up under fast idling condition when the engine is cold and idling condition is used to warm up engine at normal temperature. To sum up, when the engine is cold, the engine should be warmed up under the fast idling condition whose maximum speed is 1350 r/min; at normal temperature, it should be warmed up in idling condition to save fuel.